Age as a Prognostic Factor in Arthroscopic Drilling of Juvenile Osteochondritis Dissecans of the Knee: A National Database Review: Original Research - Isaacs, David; Baghdadi, Soroush; Lee, Alexander; Woodard, Thaddeus; Mehta, Nishank N.; Talwar, Divya; Morsink, Silas; Lawrence, J. Todd (Journal of the Pediatric Orthopaedic Society of North America, 2022)
Background: Juvenile Osteochondritis Dissecans (JOCD) is a common knee condition that can cause significant morbidity if the lesion does not heal. Arthroscopic drilling is a common surgical treatment for low-grade intact lesions, but its success rate and complications have not been well defined in a large series. Purpose: This study seeks to determine the reoperation rate and the incidence of major complications following arthroscopic drilling of JOCD lesions of the knee. Methods: A query of patients in the Pediatric Health Information System (PHIS) database from 2013 to 2018 was performed for the diagnosis and billing codes specific for arthroscopic drilling of an intact JOCD lesion. Subsequent surgical procedures on ipsilateral and contralateral knees were then analyzed for evidence of additional surgical procedures related to non-healing of the lesion. Results: We identified 1027 patients, 6-17 years of age, who underwent arthroscopic drilling as their initial surgical treatment for a diagnosis of JOCD of the knee. Within 6 months of the original surgery, 27 patients (3%) had a secondary surgery on the ipsilateral knee and 27 patients (3%) had surgery on the contralateral knee. By 2 years, 84 patients (8%) had a secondary surgery on the ipsilateral knee and 38 patients (4%) had surgery on the contralateral knee. Patient age was a significant factor in both the frequency and invasiveness of secondary surgeries, with older patients requiring repeat procedures and more invasive procedures more frequently. Less than 1% of patients underwent another surgical procedure of the knee not specifically to treat the JOCD lesion. Conclusions: The 2-year reoperation rate following drilling of an intact juvenile OCD lesion was 8%. Younger patients were less likely to undergo a subsequent procedure compared to older patients. In addition, if they did require a second procedure, younger patients were less likely to require a salvage-type cartilage procedure. The rate of complications requiring additional knee surgeries was less than 1%.